NUANSA REALITAS SOSIAL DALAM PERUMUSAN KUALIFIKASI MUJTAHID DAN MUFTI - Nurasiah Nurasiah (State Islamic University North Sumatra, 2009)
Abstract: Social Reality Nuances in Formulating the Qualifications of Mujtahid and Mufti. The relationship between law and social change is a problem faced by all legal systems and the case of Islamic law is not an exception. In formulating Islamic legal theory is found dialectic process between the formulator and with the social reality being faced not a mere following the view of the imâm. The changes of this view among other things are conducted through academic tradition of sharh which plays a role of introducing new views. The phenomenon of modernizing the preconditions of mufti and mujtahid indicate an effort of synergizing realities of condition with religious exigencies. The analysis of formulating the qualification of mujtahid and mufti apart from being supported by textual revelation it is also taken into account by considering the reality and expertise of the respective society in space and time.Kata Kunci: realitas sosial, perumusan hukum, mufti, mujtahid